EDUCATION ON ACUPRESSURE TECHNIQUES TO REDUCE MSDS IN SHALLOT FARMERS' GROUPS IN NGANJUK DISTRICT: EDUKASI TEKNIK AKUPRESURE UNTUK MENGURANGI KELUHAN MSDS PADA KELOMPOK TANI BAWANG MERAH DI KABUPATEN NGANJUK - Ratnaningtyas Wahyu Kusuma Wardani; Dwi Setiani Sumardiko (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Musculoskeletal disorders or MSDs are symptoms of muscle pain that can occur due to an incorrect position when doing work. One of the efforts to reduce the symptoms of muscle pain due to the wrong working position is acupressure massage. Acupressure is a complementary therapy and alternative therapy that has no side effects and can be used to reduce acute and chronic pain. Contains a brief background on research/ community service activities that are used as journal articles. Objective: This activity is carried out to increase understanding, knowledge, and awareness of the community, especially farmer groups about the risk of MSD symptoms and efforts to reduce pain complaints due to MSD symptoms. Method: methods of activities carried out in this community service include: 1) Pre-Activity; 2) Implementation of activities; 3) Evaluation of activities. The method used is a combination of counseling and direct practice to farmer groups. Results: improved understanding of MSDs symptoms and acupressure techniques was achieved. The knowledge of participants before receiving counseling on average was 50.0. However, participants' knowledge increased significantly after receiving counseling, which was 67.6 eligible. Conclusion: this program provides increased knowledge and understanding of MSDs and acupressure techniques in onion farmer groups.